Impact des feux sur la biomasse dans les savanes guinéo-soudaniennes du Togo - Bareremna Afelu; Kokou Jérémie Fontodji; Kouami Kokou (VertigO)
In Togo, the setting on fire of vegetation is a very common ancestral practice in farming. Beyond certain norms, the useful aspect of bush fire is superseded by its devastative effect on the ecosystems and environment. One of these effects is the fire influences on the vegetable biomass production and diversity. In front of forest fires occurrence enhancing, due to climate irregularity and human pressure on forest ecosystems, it becomes urgent to analyze the impact of fires on vegetable biomass. This study aims to assess the impacts of the iterative fires on herbaceous biomass production and diversity. To reach the goal, the demarcation of plots is based on the distribution of active fires and burned surface data and the ground measuring test. The studies took place in the savanna of protected areas. Plant layer studied is the aboveground herbaceous biomass more exposed to surface fires. It has got that main biomass is lower on the burned plots (1,034.6±249.6 g/m²) than burned plots (1,078.3±275.4 g/m²). The iterative fires lead to a main loss of production of 43.7±26.2 g/m². This loss is higher in guinean zone than sudanian’s. The total loss of herbaceous plant biomass is about 16,015±9,627.3 tons/year, equivalent to 8,007.6±4,750.5 tons of carbon rejected. Poaceae grasses, relatively more fire-resistant, prevail on the burned plots to the detriment of other herbaceous families. Indeed, in order to mitigate the rejection of household gas, to promote sustainable biodiversity management and to feel biomass needs, better comprehension of fires impacts on the dynamic of ecosystems becomes very crucial in country development planning.